Evaluation of Stunting Prevention Policy Through the "Bridal Class" Program at the Family Learning Center (Puspaga) in Keputih Village, Surabaya City - Dimas Hasanudin; Ika Devy Pramudiana; Sri Roekminiati; Sapto Pramono; Sri Kamariyah (International Journal of Scientific Multidisciplinary Research, 2024)
Stunting remains a significant health issue worldwide, particularly in developing countries like Indonesia. The Indonesian government has implemented various strategic nutrition programs to address stunting issues. Through strong collaboration among the government, communities, non-governmental organizations, and the private sector, efforts to reduce stunting are expected to proceed effectively and efficiently. This research uses scientific methods, specifically data collection and data analysis techniques, with a qualitative descriptive approach. The data collection methods include primary data, interviews, observations, and documentation. The results of the policy evaluation on stunting prevention through the "Bridal Class" program at the Family Learning Center (Puspaga) in Surabaya City show a reduction in stunting rates, which has positioned Surabaya as the city with the lowest stunting rate at the national level. Surabaya's government is also targeting Zero Stunting and Zero New Stunting by 2024. The study's findings indicate that the "Bridal Class" program has been successfully implemented in Keputih Village, Surabaya City, according to established procedures. This is evidenced by the ease of community participation in the "Bridal Class," offered through various methods, including online, offline, and hybrid formats. The stunting rate in Keputih Village, Surabaya City, has remained stable from January 2024 to October 2024, with continuous monitoring in place